FORTIFICATION OF WILD GARLIC WITH SELENIUM - Z. A. Amagova; V. H. Matsadze; N. A. Golubkina; T. M. Seredin; G. Caruso (Овощи России, 2018)
Production of functional food with significant antioxidant and anti-carcinogen activity is considered to be extremely significant in conditions of global ecological crisis. Among Allium species, wild garlic (Allium ursinum L.) along with the ordinary garlic are known to be the leaders in accumulation of natural antioxidants and sulfur-containing compounds with strong anti-carcinogen activity. Taking into consideration that Allium species belong to a group of natural accumulators of selenium, foliar biofortification of wild garlic with sodium selenate was achieved in Gudermes region of the Chechen republic. It was demonstrated that fortification of plants with selenium resulted in significant increase of chlorophyll a and b as well as carotene content, and two-fold increase of both polyphenol concentration and total antioxidant activity. Total dose of 2 mg Na2Se04 per square meter provided 14.4-fold increase of selenium content in A. ursinum leaves. Biofortification of plants with selenium resulted in 1.36, 1.28 and 1.38-fold increase of Cr, Fe and V concentration in leaves compared to leaves of non fortified plants. Leaves of A. ursinum fortified with selenium showed anomalously low Si content compared to non fortified plants. Compared to A. ursinum grown in Moscow region, wild garlic of the Chechen republic accumulated 2-fold lower levels of dry matter and 4.8-fold higher levels of monosaccharides. Compared to non fortified garlic leaves, those of A. ursinum demonstrated significantly higher levels of Cu, Fe, Mg и Zn. The results obtained suggest that A. ursinum fortified with selenium may be considered as a new functional food with strong antioxidant activity.